Energia eólica como alternativa de desenvolvimento local: sistemática socioeconômica no município de Caetité- Bahia - SANTOS, Ramosildes Anunciação dos (2016)
This thesis analyzed the wind energy as an alternative to local development and their socioeconomic systematic in Caetité in Bahia. As discussed on this matrix in the international and national scene; local development and socio-economic impacts produced by the installation of wind farms in the municipality. It was also carried out a brief diagnosis of the municipality, through the collection of secondary data and written documents analysis (plans, programs, projects and studies in the area), as well as relevant information surveys sites and institutions such as the Brazilian Institute of Geography and Statistics (IBGE), Brazilian Association of Wind Energy (ABEEólica), Secretariat of the State of Bahia (SEFAZ / BA), Superintendence of Economic and Social Studies of Bahia (SEI), etc. In addition, a field survey was conducted in the municipality of Caetité in order to identify and analyze the social and economic impacts occurring in this region with the arrival of wind farms in the perception of local stakeholders. Also, an analysis of the sociological point of view and it was verified that the economic and social impacts of the activities of these enterprises contribute significantly was made to boost local development, but the current economic and political crisis that Brazil is going through, is affecting this segment bankruptcy of some subcontractors in the region, generating unemployed women and decrease in tax collection.